2018
DOI: 10.20853/32-6-2755
|View full text |Cite
|
Sign up to set email alerts
|

Incubating a slow pedagogy in professional academic development: An ethics of care perspective

Abstract: The current neoliberal impetus in higher education has effects on all aspects of academic life, including professional academic development. These effects include increasing workloads and more casualisation of academic work, particularly teaching and a greater emphasis on quantification of scholarly outputs. The Slow movement provides an alternative way for valuing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 15 publications
0
6
0
1
Order By: Relevance
“…It is envisaged that through slowing down, 'we are able to reconnect with ourselves and others and nurture relationships to improve the quality of life and work' (Collett et al 2018:120). In academia, we have come to see the imprint of this philosophy expressed through the conceptions of Slow Science, Slow Pedagogy, Slow Ontology, Slow Philosophy and the Slow Professor (Berg & Seeber 2016;Boulous Walker 2016;Collett et al 2018;Leibowitz & Bozalek 2018;Stengers 2011;Ulmer 2017). Whilst this 'slowness' is often perceived as unproductive in academic circles, its urgency proves valuable and might rather be professed as 'differently productive' rather than unproductive (Ulmer 2017: 201).…”
Section: Unlocking the Potentials Within A Slow Pedagogy So That A mentioning
confidence: 99%
“…It is envisaged that through slowing down, 'we are able to reconnect with ourselves and others and nurture relationships to improve the quality of life and work' (Collett et al 2018:120). In academia, we have come to see the imprint of this philosophy expressed through the conceptions of Slow Science, Slow Pedagogy, Slow Ontology, Slow Philosophy and the Slow Professor (Berg & Seeber 2016;Boulous Walker 2016;Collett et al 2018;Leibowitz & Bozalek 2018;Stengers 2011;Ulmer 2017). Whilst this 'slowness' is often perceived as unproductive in academic circles, its urgency proves valuable and might rather be professed as 'differently productive' rather than unproductive (Ulmer 2017: 201).…”
Section: Unlocking the Potentials Within A Slow Pedagogy So That A mentioning
confidence: 99%
“…Drawing on Tronto's (2013) care ethic our feedback sought to open up the spaces for creativity, curiosity and caring critique. Our use of technology enabled increased opportunities for feedback, and feedback to be given at a pace and time where responses could be attentively considered (Collett, et al, 2018).…”
Section: Keeping the Focus On The Process Of Reading-writing-becomingmentioning
confidence: 99%
“…The use of online computer-assisted feedback is shown in the literature to support learner achievement effectively, and it has the potential to reduce workload in large classes (Hattie and Timperley 2007). Collett, van den Berg, Verster, and Bozalek (2018) found that technology used in a blended environment provided course participants with increased levels of feedback from peers and facilitators, keeping facilitators informed about the extent of student engagement. Boud and Molloy (2013: 20) promote the "nesting of tasks" to ensure that the feedback loop is completed, and the effects of earlier feedback can be traced.…”
Section: Formative Assessment Feedback Literacy and Technologymentioning
confidence: 99%